Project Based Learning Model as an Effective Approach to Improve Biography Writing Skills in Class X at SMK Madyatama Palembang - Ayu Puspita Indah Sari; Enny Hidajati; Yeni Ernawati; Dinda Novita novita (Cakrawala: Jurnal Pendidikan, 2026)
This research aims to determine the effect of the Project Based Learning (PjBL) model on improving the biographical text writing skills of class X students at SMK Madyatama Palembang. The research method used is quantitative with a quasi-experimental type using a one group pretest-posttest design. The research sample consisted of 33 students selected through purposive sampling technique. The data collection technique was carried out through a biographical text writing test, while data analysis used the normality test, paired sample t-test, and N-Gain test with the help of SPSS version 25. The research results showed a significant increase in students' writing skills, marked by an average pretest score of 43.3 which increased to 80 in the posttest. The results of the hypothesis test show a significance value of 0.000 <0.05, so it can be concluded that the PjBL model has a significant effect on biographical text writing skills. Apart from that, the N-Gain test result of 0.58 is in the medium category, which shows that the PjBL model is quite effective in improving students' writing skills. Thus, the PjBL model can be used as an effective and contextual learning alternative in improving biographical text writing skills.